1993
DOI: 10.1007/bf00129928
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence of pSTK1, a cryptic plasmid from Bacillus stearothermophilus TK015

Abstract: The complete nucleotide sequence of pSTK1, a cryptic plasmid isolated from B. stearothermophilus TK015, has been determined, pSTK1 has been shown to be 1883 bp in length and contain three open reading frames (ORFs), one of which has a helixturn-helix motif typical of DNA-binding proteins. Also identified was a region that can form an extensive secondary structure, which would show a high degree of similarity to palA, an origin for minus strand elongation in roiling circle replication. INTRODUCTIONThe 1.9-kbp c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…plasmids have been sequenced and described. These plasmids are pSTK1, pGS18, pGTG5, and pGTD7 (Kananavičiūtė et al, 2014;Nakayama et al, 1993;Stuknyte et al, 2008). Plasmids pBST1 (Taylor et al, 2008) and pTB19 (Oskam et al, 1991;Van der Lelie et al, 1989) have only been partially sequenced, while 10 more Geobacillus sp.…”
Section: Elements Determining Vector Replication or Chromosomal Integmentioning
confidence: 97%
“…plasmids have been sequenced and described. These plasmids are pSTK1, pGS18, pGTG5, and pGTD7 (Kananavičiūtė et al, 2014;Nakayama et al, 1993;Stuknyte et al, 2008). Plasmids pBST1 (Taylor et al, 2008) and pTB19 (Oskam et al, 1991;Van der Lelie et al, 1989) have only been partially sequenced, while 10 more Geobacillus sp.…”
Section: Elements Determining Vector Replication or Chromosomal Integmentioning
confidence: 97%
“…rstA2 is predicted to encode a polypeptide of 359 amino acids. Database searches revealed that this protein is similar to a hypothetical polypeptide (ORF3) in pSTK1, which is a cryptic plasmid of Bacillus stearothermophilus (Nakayama et al, 1993). RstA contains a Walker 'type A' motif (A /G XXXXGKT; Walker et al, 1982) located 52 amino acid residues from the C-terminus, suggesting that this protein may hydrolyse an nucleoside triphosphate.…”
Section: Figmentioning
confidence: 99%
“…The resulting construct (pGI301s) was unable to replicate in B. thuringiensis and B. subtilis, suggesting that ORF6 corresponded to the bona fide replication protein of pGI3. As mentioned above, ORF6 showed 57.4% similarity to one of the three ORFs (ORF3) present in pSTK1, a B. stearothermophilus plasmid (36). The alignment of the two proteins is shown in Fig.…”
Section: Vol 179 1997 New Family Of Rolling Circle Replicons 5003mentioning
confidence: 78%
“…Extensive database searches with the predicted products of these ORFs did not reveal any similar proteins, with the notable exception of ORF6 (see below), which showed 57.4% similarity to an ORF (ORF3) of pSTK1, a cryptic B. stearothermophilus plasmid (36). Database searches were also performed with the pGI3 DNA sequence, spliced into 500-bp fragments (with 250-bp overlap), using the GCG-BLAST program.…”
Section: Resultsmentioning
confidence: 99%